Migrant Women - Mršević, Zorica; Janković, Svetlana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
Global migratory movements are not a phenomenon involving only men. Today, they are not without women, without their experience and the specifics of women’s victimization. The steady increase in the number of women migrants is one of the characteristics of contemporary migrations in the last decades, which also applies to Serbia. At the same time as the increase in their number, the awareness is growing that they are also refugees, escaping to try to save their lives from gender-based violence. That is why the authors argue that refugee status is more suitable for them. That is why this year's National Conference on Violence against Women and Girls, held in Serbia, identifies women migrants as a particularly vulnerable group of women in Serbia. They are unprotected when moving within family groups because they are exposed to increased family violence by male family members, frustrated by travel problems and uncertain future. And when they are alone, they increasingly become victims of many, e.g. criminals, smugglers, other migrants, the same or of different nationalities, as well as members of international humanitarian organizations and even state security sector institutions. The data indicate that the states rarely or not at all prosecute an attempted rape or similar violence, but only murder. In regard to partner or domestic violence, the practice varies from case to case. Migrant women, however, increasingly report violence, but the system is still not adequately responsive.